STUDI PENGARUH PENAMBAHAN SERABUT KELAPA TERHADAP KARAKTERISTIK MARSHALL PADA CAMPURAN ASPAL PORUS - Syaviq, Muhammad Fahrus; Arifin, M. Zainul; Bowoputro, Hendi; Djakfar, Ludfi; Ambarwati, Lasmini (Rekayasa Sipil, 2018)
Porous asphalt is a solution to avoid puddles on the road because it has a pore large enough to drain the surface water. However, porous asphalt has low stability, so it is necessary to improve the Marshall stability on a porous asphalt mixture. The purpose of this research is to know the optimum composition of the asphalt content, the coconut fiber content and the coconut fiber length and to determine whether or not there is an effect of adding coconut fiber to the Marshall properties on a porous asphalt mixture. In this study, the treatment used is by making porous asphalt mixture with a variation of the asphalt content of 4%, 5% and 6% and a variation of the coconut fiber content of 0.5%, 0.75% and 1% and a variation of the coconut fiber length of 2.5 mm 5 mm and 7.5 mm to determine the optimum composition of the porous asphalt mixture. The gradation standard used in this study is the Australian Asphalt Gradient Standard and for its specifications using the Marshall characteristics of the Australian Standard (AAPA). Using the response surface method, the optimum value for the asphalt content is 4% and the optimum value of the coconut fiber is 0.75%. The addition of coconut fiber was able to increase the MQ value by 119% from 112.56 kg / mm to 246.64 kg / mm and the stability value 61.56% from 388.32 kg to 627.38 kg. However, the addition of coconut fibers decrease the VIM rate by 18.6% from 20.27% to 18.6% and the flow value by 20% from 3.24 mm to 2.7 mm. These values meet the requirements of porous asphalt?s Marshall characteristics for Australian gradation standard. It is necessary to do a further research using other gradation standard.